Communities, neighborhoods, and health expanding the boundaries of place - Burton, Linda M.; Matthews, Stephen A.; Leung, ManChui; Kemp, Susan P.; Takeuchi, David T. (Social disparities in health and health care, 2011)
Place is an important element in understanding health and health care disparities. More that merely a geographic location, place is a socio-ecological force with detectable effects on social life, independent well-being, and health. Despite the general enthusiasm for the study of place and the potential it could have for a better understanding of the distribution of health in different communities, research is at a difficult crossroads because of disagreements in how the construct should be conceptualized and measured. This edited volume incorporates an cross-disciplinary approach to the study of place, in order to come up with a comprehensive and useful definition of place. Topics covered include: Social Inequalities Historical Definitions of Place Biology and Place Rural vs. Urban Places Racialization of a Place Migration Sacred Places Technological Innovations An understanding of place is essential for health care professionals, as interventions often do not have the same effects in the clinic as they do in varied, naturalistic social settings.